Managerial motivations for UK-Czech joint ventures - Eleanor M. Maitland-Davies; Brian Kenny (Journal for East European Management Studies, 2000)
The paper examines the motives for the choice of the JV instead of other forms of investment (e.g. greenfield or licensing) in British investment in the Czech Republic. It is noted that despite popular belief, the level of uptake of JVs in the Czech Republic is low in comparison with greenfield investments. The paper identifies organisational motives (resource seeking, synergies, economic and historic), partner related motives and exogenous motives. The role of the partner in the choice of the entry mode is emphasised. Managerial implications: despite theoretical benefits of JVs to investor, these might not be accrued in practice due to the quality of the resource acquired and difficulties in management. – – In dieser Arbeit werden die Motive betrachtet, die zu einer bevorzugten Investition britischer Unternehmen in tschechische Joint Ventures im Vergleich zu anderen Investitionsformen führen. Im Artikel werden organisatorische Motive (Ressourcensuche, Synergien, ökonomische und historische Motive), partnerrelevante und exogene Motive identifiziert. Die Rolle des Partners bei der Wahl des Zusammenarbeitsmodus wird hervorgehoben. Organisatorische Relevanz: trotz der theoretischen Vorteile von Joint Ventures können diese in der Praxis oft nicht verwirklicht werden, weil die Qualität der erworbenen Ressource und Schwierigkeiten in der Organisation dagegen wirken.
Keywords: 650